Perbandingan Tingkat Kelengkapan Mandatory Disclosure dan Voluntary Disclosure Informasi Akuntansi antara Industri High-Profile dan Low-Profile - R. Widdie Andriyanto; Mega Metalia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2011)
The purpose of this research is proofing empirically whether any differences the completeness level of disclosure between high-profile industry and low-profile, along with detecting to the best of the completeness level of disclosure in various company of industry sector in Indonesian Stock exchange. Difference completeness level voluntary disclosure that significant between high profile industry and low-profile. In this research, analysis instrument that be used is Disclosure Completeness Index and mean different test Independent Sample t-Test by conviction level 95% and error level 5%. The trial result Ha1 that be done 31 various company sector industry (15 high-profile companies and 16 low-profile industry) show that Sig. (2-tailed)/2 0,05/2, with the result that Ha1 accepted. It means there are differences completeness level mandatory disclosure that significant between high-profile industry and low-profile. Whereas trial result Ha2 to 28 various company sector industry (13 high-profile companies and 15 low-profile industry) show that Sig. (2-tailed)/2 0,05/2, with the result that Ha2 rejected. This case give evidence that there are not differences between completenees level voluntary disclosure that significant between high-profile industry and low-profile.